ANALISIS EFISIENSI SALURAN PEMASARAN KARET RAKYAT DI JAMBI (Studi Kasus Desa Panerokan, Kecamatan Bajubang, Kabupaten Batanghari, Provinsi Jambi) - Tarmizi, Ahmad (Fakultas Ekonomi, UIN Maliki Malang, 2007)
The purpose of the research is to know the distribution of people rubber trading that more efficiency at Desa Panerokan. The place of research at Desa Panerokan, Kecamatan Bajubang, Kabupaten Batang Hari. The sample uses the purposive sample method. Trading margin analysis is used to know the efficiency level of trading distribution. The result of research show there are two trading distribution: 1) KUD/Auction market; 2) traditional trader KUD/Auction market has 60,2% rubber of rubber farmer, mean while, traditional trader has 39,8% rubber of farmer. The price of KUD/Auction market is higher than the traditional trader. Netto income of auction player is Rp. 300 per kg dried rubber, while netto income traditional trader is smaller about Rp. 150 per kg dried rubber